Vent’anni di memoria della Rivoluzione dei garofani negli archivi RAI (2004–2024) - Chiara Brizio Falletti di Castellazzo (RiCognizioni)
This paper examines how Rai’s coverage of the Carnation Revolution in Portugal shaped the Italian public understanding of this significant historical event. By analysing television and radio programs from the ArchivioTecheRai database between 2004 and 2024, the research explores how Rai constructed a narrative around the revolution. Five central themes are investigated: the portrayal of the revolutionary process, the legacy of Salazarism, the decolonization process, cultural resistance, and the evolving Portuguese identity. The inclusion of both Italian and Portuguese guests, with diverse experiences and perspectives, enriched Rai’s portrayal of the revolution, offering the Italian public a more nuanced understanding of the event. The study finds that Rai’s comprehensive coverage explored various aspects of the revolution and drew parallels with Italian history; however, the coverage was primarily confined to niche channels, limiting its exposure to a specific audience. The paper concludes by discussing the implications of these results for understanding the interplay between media, history, and national identity.